Transformation and Resilience of Traditional Markets Amid the Presence of E-commerce - Azis, Saipul; Bastian, Adol; M. Reski, M. Reski; Hulwati, Hulwati; Putra, Johan Septian (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
The rapid growth of e-commerce has changed the modern retail sector dramatically over the past few decades. The recent evolution of the physical retail market, driven by a shift in consumer shopping behavior to online shopping, has caused more and more traditional stores to close. This research aims to determine the transformation and resilience of traditional markets amidst the existence of E-commerce. This type of research uses a descriptive qualitative approach with analytical techniques in the form of content analysis. The research results show that in facing the challenges of this transformation, traditional markets need to adapt by entering the digital realm. Despite being faced with obstacles such as lack of digital literacy, limited resources, and infrastructure constraints, efforts to overcome these obstacles reflect the resilience of traditional markets in facing change. The resilience of traditional markets is reflected in their ability to adapt to new technology, collaborate between business players and government, increase digital literacy, innovate to maintain competitiveness, manage privacy and data security risks, and develop resources through an inclusive financial approach. The government's role is very important in encouraging transformation and facilitating the resilience of traditional markets through support policies, training programs and infrastructure facilitation. In this way, traditional markets can continue to develop, remain an integral element in the economic ecosystem, while maintaining and preserving their cultural and social identity.